Orientation of Stakeholders in the Gayo Highlands on Ecoregional Identity for Ecotourism Development of Gayo Lues District, Aceh Province - Aswita, Aswita; Avenzora, Ricky; Darusman, Dudung; Kusmana, Cecep (E-Journal of Tourism; Volume 11 Number 2 (September 2024)DO - 10.24922/eot.v11i2.80307, 2024)
Directly or indirectly, the development of ecotourism will affect the identity of the Gayo Highlands ecoregion as a living space. On the one hand, it can encourage or become a driving force for the preservation of natural resources and local culture, but on the other hand, it can exacerbate conflicts between stakeholders on ecoregional identities. Therefore, stakeholder orientation towards ecoregional identity for ecotourism development is important to be analyzed and mapped and interpreted in a comprehensive and in-depth manner, such as in Gayo Lues Regency, Aceh Province. This research on Stakeholder Orientation on Ecoregional Identity for Ecotourism Development in Gayo Lues Regency was conducted through an analysis of the perceptions, motivations and preferences of stakeholder groups; adopts the One Score One Criteria Scoring System method on seven aspects of identity, namely aspects of ecology and conservation, socio-cultural, socio-economic, socio-political, development, regional and ecotourism. The results of the analysis show that the orientation of stakeholders towards ecoregion identity is still low, out of 338 identified potential ecoregion identities, only 43% are recognized by stakeholder groups. In general, it can be said that stakeholder orientation is only focused on various ecoregional identity variables that are currently trending and have high economic value. This fact will not only result in the defragmentation of various living ecosystems, but also is latent in causing massive damage and extinction . Keywords: ecoregional, identity, conflicts, damage, extinction